Screening of musculoskeletal disorders and levels of depression in transgender people of Multan - Maryam Wisal,; Imran Ahmad Khan,; Maliha Khalid Khan, (Journal of the Pakistan Medical Association, 2024)
Objective: To perceive transgender health issues by evaluating their susceptibility to musculoskeletal problems and depression. Method: The cross-sectional, analytical study was conducted from January to April 2023at the Government Girls Comprehensive Higher Secondary School, Multan, Pakistan, a school for transgenders, and comprised subjects aged 18-40 years. Body mass index was calculated for each subject, and further data was collected using the Standard Nordic Musculoskeletal Questionnaire, Beck Depression Inventory and Numeric Pain Rating Scale. Data was analysed using SPSS 25. Results: Of the 44 subjects, 26(59%) were transgender females and 18(41%) were transgender males. The overall mean age was 25.06±1.53. There were 17(39%) subjects who had received education, and 27(61%) were illiterate. Mean depression score was 24.7±11.5, and mean body mass index was 22.9±3.16. Mean pain intensity was 5.81±2.04. Correlation analysis revealed a complex relationship among age, gender, education, occupation and health variables (p<0.01). Conclusion: Musculoskeletal disorders and the level of depression were high and correlated with the occupation of transgender individuals. Key Words: Transgender persons, Musculoskeletal disorders, Social isolation, Depression.